The Future of Humans and Emotional Machines: Narratives from Japanese Culture in the 21st Century (Routledge Contemporary Japan Series, 2025)
This book explores human‑machine interaction in Japan, providing a new focus on how and in what form people build affective bonds to new technologies. To gain insights into the feelings, identities, fears, and desires of people in our contemporary society, this book brings together perspectives from Japanese studies, cultural and literary studies, anthropology, robotics, philosophy, and game studies. Through these lenses, it reveals how narratives about machines are not merely reflections of technological capabilities but, when it comes to emotional attachment, are deeply embedded in cultural practices and social values. In addition to discussions by leading scholars in the field from around the world, this book includes two original literary contributions by award‑winning Japanese authors, Yōko Tawada and Kei’ichirō Hirano, as well as interviews with Japanese roboticists, providing readers with the rare opportunity to learn about the motivations and inspirations behind technological advances in human‑machine interaction. Shedding light on the mutual influence of academics, producers, and artists in the field of the attachment to new technologies and encouraging a dialogue between them, this book will be a valuable resource for scholars and students of Japanese studies, cultural and literary studies, and anthropology. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.